CoSe(2) Nanoparticles Encapsulated by N‐Doped Carbon Framework Intertwined with Carbon Nanotubes: High‐Performance Dual‐Role Anode Materials for Both Li‐ and Na‐Ion Batteries - Yang, Jun (Adv Sci (Weinh), 2018)
It is of fundamental and technological significance to develop dual‐role anode materials for both lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs) with high performance. Here, a composite material based on CoSe(2) nanoparticles encapsulated in N‐doped carbon framework intertwined with carbon nanotubes (CoSe(2)@N‐CF/CNTs) is prepared successfully from cobalt‐based zeolitic imidazolate framework (ZIF‐67). As anode materials for LIBs, CoSe(2)@N‐CF/CNTs composites deliver a reversible capacity of 428 mAh g(−1) even after 500 cycles at a current density of 1 A g(−1) with almost 100% Coulombic efficiency. The charge and discharge mechanisms of CoSe(2) are characterized using ex situ X‐ray diffraction and Raman analysis, from which the lithiation products of CoSe(2) are found to be Li(x)CoSe(2) and Li(2)Se, which are further converted to CoSe(2) upon delithiation. The CoSe(2)@N‐CF/CNTs composites also demonstrate excellent electrochemical performance as anode materials for SIBs with a carbonate‐based electrolyte, with specific capacities of 606 and 501 mAh g(−1) at 0.1 and 1 A g(−1) in the 100th cycle. The electrochemical performance of the anode materials is further studied by pseudocapacitance and galvanostatic intermittent titration technique (GITT) measurements. This work may be exploited for the rational design and development of dual‐role anode materials for both Li‐ and Na‐ion batteries.